2021
DOI: 10.1002/adem.202100291
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Oxide‐Dispersion‐Strengthened CoCrFeMnNi High‐Entropy Alloys with High Thermal Stability

Abstract: A nanostructured oxide‐dispersion‐strengthened (ODS) CoCrFeMnNi high‐entropy alloy (HEA) is synthesized by a powder metallurgy process. The thermal stability, including the grain size and crystal structure of the HEA matrix and oxide dispersions, is carefully investigated by X‐ray diffraction (XRD) and electron microscopy characterizations after annealing at 900 °C. The limited grain growth may be attributed to Zener pinning of yttria dispersions that impede the grain boundary mobility and diffusivity. The hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 63 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…In contrast, no such grain development can be seen in Figure 4a [27]. The authors suggested that yttrium oxide (Y 2 O 3 ) particles, which are thought to offer Zener-pinning to inhibit grain formation, may be present in varying proportions in powders from various vendors [101,102]. In actuality, oxygen and the early RE elements have a strong affinity towards inhibiting the formation of grains.…”
Section: Mg-re Alloymentioning
confidence: 99%
“…In contrast, no such grain development can be seen in Figure 4a [27]. The authors suggested that yttrium oxide (Y 2 O 3 ) particles, which are thought to offer Zener-pinning to inhibit grain formation, may be present in varying proportions in powders from various vendors [101,102]. In actuality, oxygen and the early RE elements have a strong affinity towards inhibiting the formation of grains.…”
Section: Mg-re Alloymentioning
confidence: 99%
“…In contrast, no such grain development can be seen in Figure . 4(a) [27]. The authors suggested that yttrium oxide (Y2O3) particles, which are thought to offer Zener-pinning to inhibit grain formation, may be present in varying proportions in powders from various vendors [101][102]. In actuality, oxygen and the early RE elements have a strong affinity towards inhibiting the grain formation.…”
Section: Mg-re Alloymentioning
confidence: 99%
“…In settings characterised by the presence of corrosive substances, such as chemical processing or maritime environments, the ability to resist corrosion is of utmost importance. The objective of this study is to enhance the chemical degradation and oxidation resistance of superalloys, hence assuring the durability and effectiveness of components that are subjected to harsh environments for prolonged durations [13]- [15].…”
Section: Introductionmentioning
confidence: 99%